Cannabinoid receptor 1 inhibition improves the intestinal microcirculation in experimental endotoxemia - Kianian, Mandana; Kelly, Melanie E M; Zhou, Juan; Hung, Orlando; Cerny, Vladimir; Rowden, Geoffrey; Lehmann, Christian (Clinical hemorheology and microcirculation, 2014)
INTRODUCTION: Impairment of the intestinal microcirculation in endotoxemia may cause a deterioration of the mucosal barrier function thus releasing intraluminal bacteria and their toxins into the systemic circulation. In clinical sepsis this mechanism may influence disease severity and outcome. The aim of the study was to investigate the impact of cannabinoid receptor 1 (CB1R) modulation within the intestinal microcirculation with regard to leukocyte activation and capillary perfusion, and on intestinal histology in experimental endotoxemia in rats. METHODS: Endotoxemia was induced by intravenous lipopolysaccharide (LPS) administration. We studied 5 groups of animals: controls (CON), LPS, LPS + CB1R agonist (ACEA, 2.5 mg/kg), LPS + CB1R antagonist (AM281, 2 mg/kg) and LPS + CB1R agonist (ACEA, 2.5 mg/kg) + CB1R antagonist (AM281, 2 mg/kg). Intestinal intravital microscopy (IVM) was performed two hours following LPS/placebo administration. Intestinal leukocyte adhesion in submucosal venules and functional capillary density (FCD) of the intestinal wall was quantified using IVM. Histological changes were assessed using a standardized injury score. RESULTS: After two hours of endotoxemia, we observed a significant increase of leukocyte adhesion in intestinal submucosal venules. Administration of the CB1R antagonist in endotoxemic animals significantly reduced the number of adhering leukocytes (p < 0.05). The CB1R agonist did not further increase leukocyte adhesion. FCD was significantly improved by the CB1R antagonist (p < 0.05). Administration of the CB1R agonist, ACEA, reversed the beneficial effect of the CB1R antagonist, AM281. CONCLUSIONS: CB1R inhibition significantly improved intestinal microcirculation by reducing leukocyte adhesion and increasing FCD in acute endotoxemia in rats. The data supports the involvement of the CB1R signaling in leukocyte activation during sepsis. Drugs targeting the CB1R may have therapeutic potential in systemic inflammation, such as sepsis.
Keywords: Animals; mikrocirkulace; potkani inbrední LEW; Intestines; endotoxemie; Cannabinoids; Endotoxemia; buněčná adheze; Cell Adhesion; kanabinoidy; leukocyty; střeva; Male; modely nemocí na zvířatech; Leukocytes; Microcirculation; Disease Models, Animal; krysa rodu Rattus; zvířata; mužské pohlaví; Rats, Inbred Lew; Rats